2020
DOI: 10.1101/2020.11.20.20220749
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Community Transmission of SARS-CoV-2 by Fomites: Risks and Risk Reduction Strategies

Abstract: SARS-CoV-2, the virus responsible for the COVID-19 pandemic, is perceived to be primarily transmitted via person-to-person contact, through droplets produced while talking, coughing, and sneezing. Transmission may also occur through other routes, including contaminated surfaces; nevertheless, the role that surfaces have on the spread of the disease remains contested. Here we use the Quantitative Microbial Risk Assessment framework to examine the risks of community transmission of SARS-CoV-2 through contaminate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 54 publications
(74 reference statements)
2
28
0
Order By: Relevance
“…We estimated the risk of COVID-19 infection from touching a contaminated surface using a quantitative microbial risk assessment (QMRA). 46 Infection risks ranged from 2 in 10 million to 4 in 10 thousand (mean=6.5×10 −5 , median=2.2×10 −6 ). The majority of our positive samples were not quantifiable by qPCR and were therefore treated as the theoretical qPCR limit of detection (LOD) for this analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We estimated the risk of COVID-19 infection from touching a contaminated surface using a quantitative microbial risk assessment (QMRA). 46 Infection risks ranged from 2 in 10 million to 4 in 10 thousand (mean=6.5×10 −5 , median=2.2×10 −6 ). The majority of our positive samples were not quantifiable by qPCR and were therefore treated as the theoretical qPCR limit of detection (LOD) for this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…For future work, the number of touches since last cleaning may be a more relevant metric to consider for SARS-CoV-2 RNA detection on surfaces. 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data of this survey suggest that the primary concern for respondents in selecting hand drying methods in public bathrooms during the pandemic may be avoiding contacting SARS-CoV-2 on surfaces. As studies to date have found low risk of SARS-CoV-2 transmission from fomites 8 , 9 , the public could benefit from targeted handwashing messaging highlighting this low relative transmission risk.…”
Section: Discussionmentioning
confidence: 99%
“…The RNA can remain in place for a few hours to a few days under ambient conditions. The presence of moderate SARS-CoV-2 protein content in respiratory droplets discharged by infected individuals while sneezing or coughing increases the chances of virus survival on the surfaces of contaminated fomites [ 1 ]. However, the survival time of the virus on fomites depends on temperature, humidity, virus inoculum shed on the inanimate surface and nature of the surface material.…”
mentioning
confidence: 99%